History and activities of the European-Mediterranean Seismological Centre - Rémy Bossu; Florian Haslinger; Hélène Hébert (Seismica, 2024)
The European-Mediterranean Seismological Centre (EMSC) provides rapid information on earthquakes and their effects, but does not operate seismic stations. It collects and merges parametric earthquake data from seismological agencies and networks around the world and collects earthquake observations from global earthquake eyewitnesses. Since its creation in 1975, it has developed strategies to complement earthquake monitoring activities of national agencies and coordinated its activities in Europe with its sister organisations ORFEUS and EFEHR as well as with global actors, while being part of the transformative EPOS initiative. The purpose of this article is to give a brief history of the EMSC and describe its activities, services and coordination mechanisms.